Factors Related to Practice on DPT Vaccine Distribution and Storage - Rahayu, Fitri (Jurnal Berkala Epidemiologi, 2014)
The diphtheria outbreak in Surabaya indicated that immunization program failure. Immunization is a primary preventive effort to decrease morbidity of vaccine-preventable diseases. An immunization service is very important to protect vaccine quality through the cold chain so that vaccine potency is optimal. This study aims to analyze factors related to midwives practice in the distribution and storage of the Diphtheria Pertussis Tetanus vaccine (DPT) on dynamic components in integrated health care post and village health post. This study is applying an observational approach using cross-sectional method. Populations are all village midwives in public health center East Surabaya. The numbers of samples were 38 midwives taken using simple random sampling. The dependent variable was midwives practice of DPT vaccine distribution and storage to outreach and the independent variables of this study were work duration, a history of training of cold chain, socialization, knowledge, attitude. Primary data were obtained through observation and interview. The results showed that 68.4 % of midwives practice on DPT vaccine distribution and storage at outreach is good. The Independent variable which is significantly associated with midwives practice on DPT vaccine distribution and storage at outreach is socialization about vaccine distribution and storage (p = 0.026) and value of phi and Cramer’s V = 0.431. Enhancement of socialization again is needed to village midwives as efforts to increase knowledge and attitude.